(untitled) (Iranian Journal of Kidney Diseases, 2012)
Introduction. Angiogenesis plays a role in the pathogenesis of coronary heart disease (CHD) and diabetes mellitus (DM) pathology, and certain angiogenic factors are increased by inflammation. The aim of this study was to evaluate plasma angiogenin and vascular endothelial factor A (VEGFA) levels in hemodialysis patients, as well as the effect of CHD, DM, and inflammation on these markers. Materials and Methods. Sixty-six hemodialysis patients were enrolled in the study, of whom 22 (33.3%) suffered from CHD , 22 (33.3%) from DM, and 28 (42.4%) from inflammation. They were compared with 24 healthy volunteers. Plasma angiogenin and VEGFA were assessed by means of enzyme-linked immunosorbent assay, and serum C-reactive protein was measured with an immunoturbidimetric method. These markers were compared between hemodialysis patients with and without CHD, DM, and inflammation. Results. Compared to healthy volunteers, plasma angiogenin was significantly higher in hemodialysis patients (263.57 ± 65.95 ng/mL versus 499.15 ± 175.68 ng/mL; P < .001). Similarly, plasma VEGFA was markedly increased in hemodialysis patients (median, 60.50 pg/mL; range, 280 pg/mL), compared to healthy volunteers (median, 28.84 pg/mL; range, 59.40 pg/mL; P < .001). Neither angiogenin nor VEGFA levels differed significantly between hemodialysis patients with and without CHD, DM, or inflammation. Conclusions. Plasma angiogenin and VEGFA levels are markedly increased in hemodialysis patients, but not associated with CHD, DM, or inflammation among hemodialysis patients.